Hagiographie liturgique et construction identitaire dans un néo-diocèse (XVIIIe-XIXe siècles). Le Proprium Sanctorum dans les bréviaires des diocèses français créés sous Louis XIV (La Rochelle, Alais, Blois) avant et après l’adoption de la liturgie romaine - Philippe Castagnetti (Conserveries Mémorielles)
Justifiable by the claim of the Church of France leaned on Monarchy to eradicate Protestantism, the creation under Louis XIV of the three dioceses of La Rochelle, Alais and Blois results in writing proper breviaries whose sanctoral gives importance to a lot of local saints with an apologetic purpose. The choice criterions of these saints and the litterary schemas used in matins for the biographical pieces reveal how the Church wants to keep the spirit of Counter Reformation alive by remembering the sacral mission of the king of France, increasing the conversion enterprise of the Huguenots and magnifying the cult of relics. Liturgical hagiography allows the constituting of an official religious memory in the clergy of each diocese and makes the idealization and standardization process of holiness easier. When towards the mid-19th century Roman rite takes the place of the neo-Gallican ones, calendars are simplified but the previous characteristics of the breviaries persist so much so that the eschatologic dimension of liturgy gets still clearer.